Separation of the Epitopes in a Multi-Epitope Chimera: Helical or Flexible Linkers - Kabiri, Mona; Tafaghodi, Mohsen; Saberi, Mohammad R.; Moghadam, Maliheh; Rezaee, Seyed Abdolrahim; Sankian, Mojtaba (Protein and Peptide Letters, 2020)
Background: The engineered chimeric peptides including functional multi-epitope structures fused by various peptide linkers are widely applied in biotechnological research to improve the expression level and biological activity of chimera. Objective: The aim of our study was to evaluate the effect of helical and flexible linkers on solubility, expression level and folding of multi-epitope chimera containing four epitopes of Human T Lymphotropic Virus Type 1 (HTLV-1). Methods: For this purpose, the chimera sequences connected by the helical or flexible linker were inserted into different plasmid vectors and expressed in E. coli strains. The expressed products were analyzed using SDS-PAGE and Western blot techniques. Additionally, the molecular modeling study of the chimera with helical or flexible linker was performed using iterative threading assembly refinement (I-TASSER) to attain their three-dimensional structures. Results: Comparison of the chimera expression indicated that the insertion of a flexible (GGGGS)3 linker among chimera epitopes could significantly enhance the level of expression, whereas, the low-level of chimera expression was observed for chimera containing the contiguous helical (EAAAK)5 linker. According to the results of sequence alignment and plasmid stability test, the structure and function of a consecutive helical linker among chimera epitopes were similar to porins as the outer-membrane pore-forming proteins. The molecular modeling results confirmed our experimental study. Conclusion: This investigation illustrated the key role of linker design in determining the expression level of multi-epitope chimera and conformational folding.
Keywords: purified chimera